Tea polyphenol-based submicrosphere hard carbon negative electrode material for sodium ion battery, preparation method and application

The submicrosphere hard carbon material prepared by tea polyphenols and amino acids under hydrothermal conditions has solved the problem of defects in the high-temperature carbonization process of traditional phenolic resin materials, and achieved efficient and safe sodium ion battery negative electrode material, which improved the Energy density and rate performance of the battery.

CN119176543APending Publication Date: 2024-12-24CHENGDU SIWEN LINGYUN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411325434.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Traditional phenolic resin hard carbon materials produce surface defects and high porosity during high-temperature carbonization, resulting in low Coulomb efficiency and reversible capacity of sodium ion batteries. Commonly used phenol sources such as phenol and resorcinol are toxic and difficult to meet safety and environmental Friendly demand.

Method used

Tea polyphenols are used as phenol source, combined with amino acids and formaldehyde to prepare submicrosphere hard carbon negative electrode materials through hydrothermal method, and a new phenolic resin with high crosslinking is formed through benzoxazine chemical reaction, which regulates the microstructure and morphology of the material. , improve Na+ storage performance.

Benefits of technology

The sodium ion battery negative electrode material with high first-term efficiency, reversible capacity and good cycle life has been achieved, which reduces the porosity and defects of the material, improves the energy density and rate performance, and is safe and non-toxic to use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176543A_ABST
    Figure CN119176543A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion battery negative electrode materials, and particularly relates to a tea polyphenol-based submicrosphere hard carbon negative electrode material for a sodium ion battery, a preparation method and application. A preparation method of a tea-polyphenol-based submicrosphere hard carbon negative electrode material for a sodium-ion battery is characterized by comprising the following steps: S1, adding amino acid and formaldehyde into a tea polyphenol aqueous solution, stirring in a constant-temperature water bath, reacting in a drying oven, separating, precipitating, washing and drying to obtain a carbon precursor; and S2, performing high-temperature sintering on the carbon precursor obtained in the S1 to obtain the submicrosphere hard carbon negative electrode material. The hard carbon negative electrode material disclosed by the invention is high in compaction density, high in first efficiency, high in reversible specific capacity and good in cycling stability, and has spherical morphology with uniform size and full shape, and the preparation method disclosed by the invention is simple to operate, high in safety and good in repeatability, and can be applied as a sodium ion battery negative electrode material in large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials for sodium ion batteries, and in particular relates to a submicrosphere hard carbon negative electrode material for sodium ion batteries based on tea polyphenols, a preparation method and an application thereof. Background Art

[0002] In recent years, energy and environmental issues have promoted the vigorous development of new energy technologies, including chemical power sources. In order to meet the application needs of future electric vehicles, mobile devices and other fields, chemical power sources need to have larger capacity and higher energy density. Sodium-ion batteries are the biggest candidate to replace lithium-ion batteries because of their abundant sodium resources and great potential for charge storage. Suitable sodium storage materials will greatly promote the development of sodium-ion batteries. Among them, hard carbon is considered to be the most promising negative electrode material for sodium-ion batteries due to its low cost, good conductivity, high sodium storage capacity, environmental friendliness and low redox potential.

[0003] As a common commercial hard carbon precursor, traditional phenolic resin has controllable synthesis, easy adjustment of microstructure and good electrochemical performance after carbonization. However, it still has the following problems, such as the limited cross-linking degree of the derivative carbon will release a large number of small gas molecules during the high-temperature carbonization process, resulting in large surface defects and high porosity in the hard carbon structure, which increases the Na + The irreversible adsorption of phenol leads to low coulombic efficiency and reversible capacity. Secondly, the toxicity and carcinogenicity of commonly used synthetic phenol sources, such as phenol and resorcinol, will have a certain impact on the environment and human safety. At the same time, the low discharge platform (0.01-0.1V) of hard carbon negative electrode materials is very important for achieving high energy / power density of sodium ion batteries. At present, the platform capacity of phenolic resin hard carbon is low and cannot meet the existing requirements. Therefore, there is an urgent need for low-cost, safe and non-toxic raw materials as new phenol sources, and to regulate the microstructure of hard carbon materials at the molecular level to prepare spherical sodium ion negative electrode materials with high first efficiency, high reversible capacity, high platform capacity and good cycle life. Summary of the invention

[0004] In view of the shortcomings and problems of the prior art, the present invention provides a method for preparing a submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols, comprising the following steps:

[0005] S1: adding amino acids and formaldehyde to the tea polyphenol aqueous solution, stirring in a constant temperature water bath, placing in an oven for reaction, separating the precipitate, washing, and drying to obtain a carbon precursor;

[0006] S2: The carbon precursor obtained in S1 is subjected to high temperature sintering to obtain a submicrospherical hard carbon negative electrode material.

[0007] Furthermore, the amino acid described in S1 is any one of L-methionine, L-cysteine, L-glutamic acid, L-aspartic acid, and L-asparagine.

[0008] Furthermore, the mass ratio of the amino acid to tea polyphenols described in S1 is 0.25-2, and the dosage ratio of formaldehyde to amino acid is 0.6-4 ml:1 g.

[0009] Furthermore, the stirring temperature in S1 is 15 to 40° C., and the stirring time is 10 to 30 min.

[0010] Further, the reaction temperature in the oven described in S1 is 60-120° C., and the reaction time is 10-12 h. Further, the drying temperature described in S1 is 50-60° C., and the drying time is 12 h to 24 h.

[0011] Furthermore, the sintering temperature described in S2 is 1200-1400° C., the sintering rate is 3-5° C. / min, and the holding time is 2 h.

[0012] A submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols. The submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols is a uniform spherical particle with a full shape.

[0013] The invention discloses an application of a submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols. The material is applied in the preparation of a negative electrode material for a sodium ion battery.

[0014] Technical Effects

[0015] (1) The present invention provides a submicrosphere hard carbon negative electrode material for sodium ion batteries based on tea polyphenols. The present invention uses non-toxic and cheap natural plant tea polyphenols to replace phenol / resorcinol and other commonly used toxic phenol sources. The addition of amino acids as amine sources increases the three-dimensional crosslinking degree of phenolic resins, which has higher tap density and compaction density than traditional phenolic resins without amino acids, which is beneficial to improve the volume energy density of the negative electrode. In addition, the introduction of amino acid R groups can also affect the microstructure of phenolic resins to improve their Na storage capacity. + Performance, such as adding L-glutamic acid to introduce a large number of carboxyl groups is beneficial to increase the additional Na storage during charging and discharging + sites, a sodium ion negative electrode material with high first efficiency, high reversible specific capacity and good cycle stability can be obtained.

[0016] (2) The preparation method of a submicron-sized hard carbon negative electrode material for a sodium ion battery based on tea polyphenols provided by the present invention is simple to operate, highly safe, and has good repeatability. A uniform submicron-sized hard carbon material is prepared by a one-pot hydrothermal method in a mild, pressure-free environment. The high packing density of the spherical particles can shorten the Na + The transmission path can increase the Na+ The transport kinetics of the electrodes can be optimized to improve the rate performance and conductivity of the electrodes.

[0017] (3) Through the application of a tea polyphenol-based submicrosphere hard carbon negative electrode material for sodium ion batteries provided by the present invention, the present invention can adjust the morphology and microstructure of the material by changing the type, concentration, reaction temperature and time of the raw materials, and can obtain a sodium ion negative electrode material with excellent performance at a suitable carbonization temperature. The material is a new type of phenolic resin with a nitrogen-oxygen heteroatom six-membered ring structure formed by ring-opening polymerization using natural tea polyphenols as a phenol source and amino acids as an amine source, which react with formaldehyde under heating conditions to produce a benzoxazine chemical reaction. It not only has the advantages of traditional phenolic resins, but also has a high degree of crosslinking, which makes the prepared material have low porosity and few defects. At the same time, nitrogen atoms and oxygen-containing functional groups are introduced, which is conducive to the application as a negative electrode material for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0019] Figure 1 Schematic diagram of the synthesis mechanism of benzoxazine resin monomer;

[0020] Figure 2 is a scanning electron microscope image of Examples 1-5 of the present invention;

[0021] Figure 3 is a cycle stability diagram of Example 1 of the present invention at a current density of 0.1 A / g;

[0022] Figure 4 The compacted density and resistivity of Example 1 of the present invention and Comparative Example 1 tested at 10-200 MPa;

[0023] Figure 5 It is a first cycle charge and discharge curve diagram of Examples 1-5 of the present invention and Comparative Example 1 at a current density of 0.05 A / g;

[0024] Figure 6 is a rate performance diagram of Examples 1-5 of the present invention and Comparative Example 1 at different current densities;

[0025] Figure 7 is a first cycle charge and discharge curve diagram of Examples 1, 6 and 7 of the present invention at 0.05 A / g;

[0026] Figure 8It is a scanning electron microscope image of Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with Examples 1-7 of the present invention and Comparative Examples 1-2 and the attached Figures 1 to 8 , the technical solution of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The present invention provides a method for preparing a submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols, comprising the following steps:

[0029] S1: First, natural tea polyphenols are added to deionized water to form a tea polyphenol aqueous solution, and then amino acids are added to the tea polyphenol aqueous solution, and the mixture is stirred in a constant temperature water hot pot to completely dissolve, and then formaldehyde solution is dropped to obtain a mixed solution, and the mixed solution after mixing and stirring is placed in an oven for reaction, and the precipitate is separated by suction filtration and multiple water / ethanol washing, and the hard carbon precursor is obtained after drying in a blast oven;

[0030] S2: Place the alumina crucible containing the dried precursor in a tubular furnace in an argon atmosphere, heat it to 1200-1400°C at a heating rate of 3-5°C / min, cool it at a rate of 5°C / min above 800°C, and then naturally cool it to room temperature to obtain a submicronized hard carbon negative electrode material for sodium ion batteries based on tea polyphenols.

[0031] Example 1

[0032] S1: Add 1g of tea polyphenols to 80ml of deionized water, stir at room temperature for 10min until completely dissolved to form a clear red tea polyphenol aqueous solution; weigh 1g of L-glutamic acid and add it to the tea polyphenol aqueous solution, stir at 40℃ for 30min to completely dissolve it; drop 1ml of formaldehyde solution into the reaction solution, mix and stir the three for 20min to obtain a mixed solution, place the mixed solution in an oven at 90℃ for 12h; filter the reaction product by suction, wash it with water / ethanol twice respectively, and dry the separated precipitate in a 60℃ forced air oven for 12h to obtain a hard carbon precursor;

[0033] S2: The alumina crucible containing the precursor is placed in a tubular furnace in an argon atmosphere, heated to 1300°C at a heating rate of 5°C / min and kept warm for 2 hours. After cooling to room temperature, a submicrosphere hard carbon negative electrode material for sodium ion battery based on tea polyphenols is obtained, which is denoted as Glu-1300. The tap density of the Glu-1300 hard carbon material prepared in Example 1 is tested, and the result is 0.718 g / cm3 ; Further resistivity and compaction density tests were performed under variable pressure mode, and the results were 0.0122Ω*cm and 1.123g / cm at 200MPa respectively. 3 .

[0034] from Figure 1 It can be seen that tea polyphenols undergo a Mannich reaction with amino acids and formaldehyde under appropriate hydrothermal conditions to form benzoxazine resin monomers, which then undergo ring-opening curing during the subsequent heating process, thereby generating a new type of network resin containing nitrogen atoms and oxygen-containing functional groups, which is a resin-type hard carbon precursor.

[0035] from Figure 3 It can be seen that Figure 3 This is the cycle stability diagram of Example 1. The half-cell assembled with the sodium metal sheet of Example 1 was activated for two cycles at a current density of 0.05A / g, and then the cycle test was performed at a current density of 0.1A / g. After 200 cycles, the coulombic efficiency of Example 1 was close to 99.5%, which shows that the reversible performance of the sample is good. After 200 cycles, the charge capacity was 283.7mAh / g, and the corresponding capacity retention rate was as high as 95%.

[0036] Example 2

[0037] S1: Add 0.5g tea polyphenols to 80ml deionized water, stir at room temperature for 10min until completely dissolved to form a clear red tea polyphenol aqueous solution; weigh 1g L-aspartic acid and add it to the tea polyphenol aqueous solution, stir at 25℃ for 10min to completely dissolve it; drop 1ml formaldehyde solution into the reaction solution, mix and stir the three for 20min to obtain a mixed solution, place the mixed solution in an oven at 90℃ for 12h; filter the reaction product by suction, wash it with water / ethanol twice respectively, and dry the separated precipitate in a 60℃ forced air oven for 12h to obtain a hard carbon precursor;

[0038] S2: Place the alumina crucible containing the precursor in a tubular furnace in an argon atmosphere, heat it to 1300°C at a heating rate of 5°C / min and keep it warm for 2 hours. After cooling to room temperature, a submicrosphere hard carbon negative electrode material for sodium ion batteries based on tea polyphenols is obtained, which is recorded as Asp-1300.

[0039] Example 3

[0040] S1: Add 0.5g tea polyphenols to 80ml deionized water, stir at room temperature for 10min until completely dissolved to form a clear red tea polyphenol aqueous solution; weigh 1g L-asparagine and add it to the tea polyphenol aqueous solution, stir at 30℃ for 30min to completely dissolve it; drop 1ml formaldehyde solution into the reaction solution, mix and stir the three for 10min to obtain a mixed solution, place the mixed solution in an oven at 90℃ for 12h; filter the reaction product by suction, wash it with water / ethanol twice respectively, and dry the separated precipitate in a 60℃ forced air oven for 12h to obtain a hard carbon precursor;

[0041] S2: Place the alumina crucible containing the precursor in a tubular furnace in an argon atmosphere, heat it to 1300°C at a heating rate of 5°C / min and keep it warm for 2 hours. After cooling to room temperature, a submicrosphere hard carbon negative electrode material for sodium ion batteries based on tea polyphenols is obtained, which is recorded as Asn-1300.

[0042] Example 4

[0043] S1: Add 0.5g tea polyphenols to 80ml deionized water, stir at room temperature for 10min until completely dissolved to form a clear red tea polyphenol aqueous solution; weigh 1g L-methionine and add it to the tea polyphenol aqueous solution, stir at 15℃ for 20min to completely dissolve it; drop 1ml formaldehyde solution into the reaction solution, mix and stir the three for 10min to obtain a mixed solution, place the mixed solution in an oven at 90℃ for 12h; filter the reaction product by suction, wash it with water / ethanol twice respectively, and dry the separated precipitate in a 60℃ forced air oven for 12h to obtain a hard carbon precursor;

[0044] S2: Place the alumina crucible containing the precursor in a tubular furnace in an argon atmosphere, heat it to 1300°C at a heating rate of 5°C / min and keep it for 2 hours. After cooling to room temperature, a submicrosphere hard carbon negative electrode material for sodium ion batteries based on tea polyphenols is obtained, which is recorded as Met-1300.

[0045] Example 5

[0046] S1: Add 0.25g tea polyphenols to 40ml deionized water, stir at room temperature for 10min until completely dissolved to form a clear red tea polyphenol aqueous solution; weigh 0.5g L-cysteine ​​and add it to the tea polyphenol aqueous solution, stir at 25℃ for 20min to completely dissolve it; drop 0.5ml formaldehyde solution into the reaction solution, mix and stir the three for 10min to obtain a mixed solution, place the mixed solution in an oven at 90℃ for 10h; filter the reaction product by suction, wash it with water / ethanol twice respectively, and dry the separated precipitate in a 60℃ forced air oven for 12h to obtain a hard carbon precursor;

[0047] S2: Place the alumina crucible containing the precursor in a tubular furnace in an argon atmosphere, heat it to 1300°C at a heating rate of 5°C / min and keep it at that temperature for 2 hours. After cooling to room temperature, a submicrosphere hard carbon negative electrode material for sodium ion batteries based on tea polyphenols is obtained, which is recorded as Cys-1300.

[0048] from Figure 2 It can be seen that Figure 2 This is a scanning electron microscope image of the tea polyphenol-based submicrosphere hard carbon negative electrode material for sodium ion battery of Examples 1-5, Figure 2 (a) Glu-1300, Figure 2 (b) Asp-1300, Figure 2 (c) Asn-1300, Figure 2 (d) Met-1300, Figure 2 (e) is Cys-1300. Figure 2 It can be seen that all samples are uniform spherical powders after carbonization, with good dispersion, no agglomeration, smooth surface and no obvious defects, and the particle size is between 500nm-1.5μm. It can be seen that the present invention can successfully prepare submicron spherical hard carbon negative electrode materials with regular morphology, and the size of the required spherical hard carbon can be adjusted according to the different types of amino acids added.

[0049] Example 6

[0050] S1: Add 1g of tea polyphenols to 80ml of deionized water, stir at room temperature for 10min until completely dissolved to form a clear red tea polyphenol aqueous solution; weigh 1g of L-glutamic acid and add it to the tea polyphenol aqueous solution, stir at 40℃ for 30min to completely dissolve it; drop 1ml of formaldehyde solution into the reaction solution, mix and stir the three for 20min to obtain a mixed solution, place the mixed solution in an oven at 90℃ for 12h; filter the reaction product by suction, wash it with water / ethanol twice respectively, and dry the separated precipitate in a 60℃ forced air oven for 12h to obtain a hard carbon precursor;

[0051] S2: Place the alumina crucible containing the precursor in a tubular furnace in an argon atmosphere. During carbonization, heat it to 1200°C at a heating rate of 5°C / min and keep it warm for 2 hours. After cooling, a submicrosphere hard carbon negative electrode material for sodium ion batteries based on tea polyphenols is obtained, which is recorded as Glu-1200.

[0052] Example 7

[0053] S1: Add 1g of tea polyphenols to 80ml of deionized water, stir at room temperature for 10min until completely dissolved to form a clear red tea polyphenol aqueous solution; weigh 1g of L-glutamic acid and add it to the tea polyphenol aqueous solution, stir at 40℃ for 30min to completely dissolve it; drop 1ml of formaldehyde solution into the reaction solution, mix and stir the three for 20min to obtain a mixed solution, place the mixed solution in an oven at 90℃ for 12h; filter the reaction product by suction, wash it with water / ethanol twice respectively, and dry the separated precipitate in a 60℃ forced air oven for 12h to obtain a hard carbon precursor;

[0054] S2: Place the alumina crucible containing the precursor in a tubular furnace in an argon atmosphere. During carbonization, heat it to 1400°C at a heating rate of 5°C / min and keep it warm for 2 hours. After cooling, a submicrosphere hard carbon negative electrode material for sodium ion batteries based on tea polyphenols is obtained, which is recorded as Glu-1400.

[0055] Comparative Example 1

[0056] The specific preparation method is the same as that of Example 1, except that in Example 1, 1 g of L-glutamic acid is not added, and tea polyphenols and formaldehyde are directly reacted, which is recorded as HC-1300. The tap density of the HC-1300 hard carbon negative electrode material prepared in Example 1 is 0.663 g / cm 3 The resistivity and compaction density at 200 MPa are 0.0163 Ω*cm and 1.053 g / cm 3 After adding glutamic acid, the tap density and compacted density of Example 1 were increased to 0.718 g / cm 3 and 1.123 g / cm 3 , and has better conductive properties, such as Figure 4 shown.

[0057] from Figure 5 It can be seen that Figure 5 It is the first cycle charge and discharge curve of Examples 1-5 of the present invention and Comparative Example 1 tested at 0.05A / g, which shows a typical high-temperature carbonization hard carbon curve, that is, it contributes a large platform capacity in the low voltage range of 0.01-0.1V. Combined with the data in Table 1, it can be obtained that Example 1 in which L-glutamic acid is added has the highest first efficiency of 88.3% and a reversible charge capacity of 324.9mAh / g. The platform area capacity it provides is also the largest at 227.7mAh / g, which is beneficial to increase the energy density of the battery. The performance of all Examples 1 to 5 is better than that of Comparative Example 1 without the addition of amino acids. It can be seen that the use of amino acids in the present invention to regulate the microstructure at the molecular level can effectively improve the sodium storage performance of the negative electrode of the sodium ion battery.

[0058] Table 1 Electrochemical performance of Examples 1 to 5 and Comparative Example 1

[0059]

[0060] Figure 6 The rate performance of Examples 1-5 and Comparative Example 1 at different current densities of 0.05, 0.1, 0.2, 0.5, 1, and 2 A / g. It can be seen that Examples 1-5 not only have a significantly higher specific charge capacity than Comparative Example 1 at a high current density of 2 A / g, but also when the current density is restored to 0.1 A / g, the specific capacity can still be restored to 306.2 mAh / g, 298.9 mAh / g, 272.2 mAh / g, 279.9 mAh / g, and 284.8 mAh / g, respectively. Among them, Example 1 has the highest specific charge capacity of 233 mAh / g at a high current density of 2 A / g, which is 50 mAh / g higher than Comparative Example 1, and has excellent rate performance.

[0061] Figure 7 1 is the first cycle charge and discharge curve of Examples 1, 6 and 7 at 0.05 A / g, and Table 2 can show their specific sodium storage capacity.

[0062] Table 2 Electrochemical performance of Examples 1, 6 and 7

[0063]

[0064]

[0065] When the carbonization temperature is reduced from 1300°C to 1200°C, the sodium storage performance of Example 6 is also reduced to a first cycle charge capacity of 260.5 mAh / g and a first efficiency of 81.0%. The higher performance of Example 5 than that of Example 6 is because as the carbonization temperature increases, the number of defects in the hard carbon material decreases, resulting in a reduction in irreversible sodium storage points. As the temperature is further increased to 1400°C, the increase in graphitization leads to a decrease in interlayer spacing, which affects the Na + The de- / insertion process occurs, so the initial charge specific capacity of Example 7 is reduced to 306.2 mAh / g.

[0066] It can be seen that the present invention can adjust the sodium storage performance of the prepared submicrospherical hard carbon by changing the carbonization temperature, and taking the addition of L-glutamic acid as an example, it can be seen that the carbonization temperature of 1300° C. is more appropriate.

[0067] Comparative Example 2

[0068] The specific preparation method is the same as that of Example 1, with the specific difference being that the reaction temperature in the oven in Comparative Example 2 is 30° C., recorded as Glu-30-1300.

[0069] Figure 8This is a scanning electron microscope image of comparative example 2. The hydrothermal reaction temperature is 30°C. The lower reaction temperature cannot provide enough energy to make the crystal nuclei grow uniformly, resulting in the appearance of molten spherical and regional honeycomb structures, which further illustrates the necessity of the reaction conditions for preparing submicrosphere hard carbon materials provided by the present invention.

[0070] Due to the poor thermal stability of tea polyphenols, foaming and expansion easily occur during direct pyrolysis, which makes its natural microstructure easily destroyed and its morphology uncontrollable. In the field of negative electrode materials for sodium ion batteries, the spherical morphology is more suitable for uniform coating of the pole piece and improving the compaction density of the pole piece to a certain extent. In addition, the regular spherical structure has a uniform conduction path for electrons and ions, which is more conducive to improving the rate performance of the electrode material. In order to achieve a spherical morphology, one of the commonly used technical means is to conduct a phenolic condensation reaction between polyphenols and aldehydes, but whether its specific morphology is uniform and regular is affected by the type and proportion of raw materials and reaction conditions.

[0071] On this basis, the present invention uses natural tea polyphenols as a phenol source and amino acids as an amine source, and the two react with formaldehyde under heating conditions to produce a benzoxazine chemical reaction to prepare a new spherical resin with uniform size and full shape, and its tap density and compaction density are significantly improved; compared with traditional phenolic resins, it has lower porosity and defects, which is conducive to improving its first coulomb efficiency and reversible capacity as a negative electrode of a sodium ion battery. It can be seen from the actual test performance that the first coulomb efficiency without the addition of amino acids is only 77.7%, and the reversible charge specific capacity is 255.5mAh / g. After the addition of amino acids, Examples 1 to 5 have a significant improvement, which produces unexpected technical effects.

[0072] In the selection of components, considering that the electrochemical performance of sodium ions can be improved by introducing heteroatom defects and active sites, the addition of amino acids can not only increase the three-dimensional cross-linking degree of the resin, but also the R group with active groups can affect the microstructure of the submicrospheres to improve their Na storage capacity. + Performance: For example, L-glutamic acid can introduce two carboxyl groups, which can cross-link with hydroxyl groups to form ester groups, which can produce closed pores at high temperatures, thereby increasing additional specific capacity; for example, L-cysteine ​​introduces heteroatom S, which can expand the interlayer spacing while increasing the defective active sites of the material.

[0073] The present invention adopts a higher reaction temperature (60-120°C) and a longer reaction time (10-12 hours) to prepare the precursor. The high temperature and stable hydrothermal environment is conducive to the formation of more crosslinking points, further improving the crosslinking degree of the polymer and enhancing the interaction force between molecules (such as π-π bonds and hydrogen bonds). This optimization is conducive to the structural stability of the precursor during the subsequent high temperature carbonization process.

[0074] In the preparation method of submicrospherical hard carbon materials, the invention not only selects suitable raw materials, proportions, reaction conditions, etc. in the preparation of the precursor to obtain a new phenolic resin with the target morphology and structure; in the subsequent carbonization process, in order to obtain a "platform-type" hard carbon material that is conducive to achieving high energy / power density of sodium ion batteries, sintering is carried out at a high temperature of 1200-1400°C, and the carbonization temperature is explored to obtain the optimal embodiment, namely Embodiment 1.

Claims

1. A method for preparing a submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols, characterized in that: The following steps are involved: S1: adding amino acid and formaldehyde to the tea polyphenol aqueous solution, stirring in a constant temperature water bath, placing in an oven for reaction, separating the precipitate, washing, and drying to obtain a carbon precursor; S2: The carbon precursor obtained in S1 is subjected to high temperature sintering to obtain a submicrospherical hard carbon negative electrode material.

2. The method for preparing a submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols according to claim 1, characterized in that: The amino acid described in S1 is any one of L-methionine, L-cysteine, L-glutamic acid, L-aspartic acid, and L-asparagine.

3. The method for preparing a submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols according to claim 1, characterized in that: The mass ratio of amino acids to tea polyphenols described in S1 is 0.25-2, and the dosage ratio of formaldehyde to amino acids is 0.6-4 ml:1 g.

4. The method for preparing a submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols according to claim 1, characterized in that: The stirring temperature described in S1 is 15 to 40° C., and the stirring time is 10 to 30 minutes.

5. The method for preparing a submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols according to claim 1, characterized in that: The reaction temperature in the oven described in S1 is 60-120° C., and the reaction time is 10-12 h.

6. The method for preparing a submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols according to claim 1, characterized in that: The drying temperature described in S1 is 50-60° C., and the drying time is 12 h to 24 h.

7. The method for preparing a submicrosphere hard carbon negative electrode material for a sodium ion battery based on tea polyphenols according to claim 1, characterized in that: The sintering temperature described in S2 is 1200-1400°C, the sintering rate is 3-5°C / min, and the holding time is 2h.

8. A submicrosphere hard carbon negative electrode material for sodium ion battery based on tea polyphenols obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The tea polyphenol-based submicrosphere hard carbon negative electrode material for sodium ion batteries is a uniform spherical particle with a full shape.

9. The use of a submicrosphere hard carbon negative electrode material for sodium ion battery based on tea polyphenols according to claim 8, characterized in that: The material is used in preparing negative electrode materials for sodium ion batteries.